Follicular dynamics of glycerophospholipid and sphingolipid metabolisms in polycystic ovary syndrome patients. Issue 185 (January 2019) - Liu, Lingyan; Yin, Tai-lang; Chen, Yu; Li, Yinghuan; Yin, Lu; Ding, Jinli; Yang, Jing; Feng, Huai-L
Graphical abstract: Highlights: UPLC-MS detected glycerolipid, glycerophospholipids, sphingolipids, and carboxylic acids were different in PCOS FF. Reduced PGP and TG were related to lower fertilization rate in PCOS. Decreased sphingolipids, glycerophospholipids, and fluctuated fatty acyls were related to other ART results. Follicular disturbance of glycerolipid, glycerophospholipid, sphingolipid metabolism in PCOS affected ART results. Abstract: Polycystic ovary syndrome (PCOS) is a common heterogeneous disease, affecting up to 5–10% women at reproductive age. Although PCOS patients could produce morphologically normal metaphase II oocytes undergoing assisted reproductive techniques (ART), oocyte developmental competence and embryo development have been impaired in following in-vitro fertilization (IVF) steps. Follicular fluid (FF) provides a variety of information in oocyte environment when oocytes grow. In the present work, based on ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS), the metabolic signatures of PCOS FF have been compared with healthy women using untargeted metabolomics approach. Significant abundance differences of a series of glycerolipid, glycerophospholipids, sphingolipids, and carboxylic acids have been discovered. Among them, reduced levels of phosphatidylglycerolphosphate (PGP) and a triglyceride (TG) were highly related to the lower fertilization rate in PCOS; increased abundance of lysoPE and decreased amount of PC were significantly correlated with LH/FSH (ratio of luteinizing hormone to follicle stimulating hormone). Some metabolites, including decreased sphingolipids, glycerophospholipids, and fluctuated fatty acyls, also performed close relationship with other ART and clinical results. We concluded that dysfunctions in the metabolism of glycerolipid, glycerophospholipid, sphingolipid, and glycosphingolipid biosynthesis in PCOS patients' follicles play a non-ignorable role in declining the 2 pronuclei (PN) fertilization rate during IVF procedure.